Positive Image of the Public Civil Servants as Basis of Development of Administrative Culture - Valentina Nikolaevna Orlova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The author has proved a problem of designing of image of the public civil servants in system of public administration. Factors of development of administrative culture of the case of officials through communicative technologies are revealed. The role of modern mass media in system of professional development of the public civil servants is opened. The importance of effective long-term strategy of management of positive image of the public civil servant is considered that provides transparency and coherence of interaction between society and authorities.